SUSTAINABILITY DISCLOSURE evidence from mandatory reporting regulation in. (ROUTLEDGE, 2026)
Sustainability Disclosure examines the evolution of sustainability disclosure resulting from the implementation of mandatory reporting legislation within the European Union using the evidence from the Non-Financial Reporting Directive (NFRD) and Corporate Sustainability Reporting Directive (CSRD). Overall, the findings underscore the significance of mandatory reporting legislation in increasing the number of companies disclosing their social and environmental impact, as well as broadening the scope of reporting.Addressing the current topics of mandatory regime for sustainability disclosure, the book offers important insights for academic scholars, regulators, and policy makers indicating strength and weaknesses of NFRD with potential feedback for the recently introduced CSRD regulation. In addition, the analysis of the evidence from companies listed on the Warsaw Stock Exchange (WSE) delivers interesting lessons for practitioners, managers, and auditors responsible for implementing mandatory reporting legislation at the company level. Finally, the book would be helpful for Ph.D. candidates and students of management and organisation, economics, finances as well as legal studies willing to develop their understanding about sustainability disclosure.
Keywords: Sustainable development reporting -- European Union countries.; elektronické knihy; electronic books